Jenis Arthropoda Goa Gumbasalu Kecamatan Bambalamotu Kabupaten Mamuju Utara Dan Pengembangannya Sebagai Media Pembelajaran - Rosnita Rosnita; Achmad Ramadhan; Hartono D Mamu (Mitra Sains, 2016)
The purpose of this study was to identify and describe the types of arthropods in Gumbasalu cave Bambalamotu District of North Mamuju regency. The result of this study then developed into biology teaching media in the form of a paperback book and audio-visual media. This study was held in form of descriptive research and development using 4D design. Sampling for Arthropods used direct collection techniques and pitffal trap then identified using a key book determination. Results of the study found 16 species of arthropods, which consists of 2 class of crustasea, 6 class of insect, 3 class of arachnid and 5 class of Myriapoda as for the type found is Parathelphusa sp, Macrobrachium lar. F, Rhaphidophora sp, Apis sp, sp Lophobaris, Formica rufa. L, Lepisma sp, sp Antomeris, Heteropoda sp, sp Charon, Heteropoda beroni, Scutigera sp, Scolopendra sp, sp Julus, Nerceus sp, Julus sp. Results were then used as a paperback book and audio-visual media. These two media then validated by the validation results for the paper back book content expert (83.3%), media experts (86.15%), design experts (82.8% ), and audio-visual media experts (93.3%), and then tested on the test results of students with small group for a paperback book (85.2%), testing a large group (86.4%). For audio visual media the percentage result was in a small group (83.51%), in a large group (87.4%). The result of this study shows that learning media in the form of a paperback book and audio-visual is proper for use.